The Child Self-Reliance Character Education Model at the Aisyiyah Orphanage in Klaten - Saepul Anwar; Masithoh Ayu Kusumandari (Educan : Jurnal Pendidikan Islam, 2021)
Self-sufficiency has a significant impact on a child's future, if not responded to properly can have a detrimental effect on the child's psychological development. Because at the time they were looking for their hobby. For this reason, parents should therefore provide guidance to the child to prepare his or her future life. Some children are not as lucky as children in general. Few children in Indonesia have a family situation because they are neglected. In this case, the child does not have an example or a person to whom self-sufficiency education is provided. In this regard, orphans must have a role to play in the formation of a self-sufficient person in a child without relatives. The Orphanage of Aisha Klaten is one of the private social institutions in the field of maintenance and rearing of neglected children. They are raised and directed in their daily lives, hoping that the self-sufficiency education taught to them can be applied in everyday life so that they can become self-contained personalities.The objectives of this research: on the principle of self-sufficiency education, how to apply this principle, the factors that advocate and the discouraging factors of caregivers in the formation of self-sufficiency in children in the orphanage and how to analyze them, the effects of these steps in the education of self-sufficiency. This research is a qualitative descriptive study. For the data the researcher used: 1) the interview. 2) Note. 3) Written documents. Analysis of research researcher used: 1) data analysis 2) data presentation 3) extraction/verification.The results of the research showed that the pattern of self-sufficiency education carried out by the orphanage in Aisha is in the form of the formation of a personal self-sufficiency of children using organized activities and problem solving per se and forming a discipline with the provision of punishment and the formation of a responsible character while giving responsibility to the head of the chamber. Factors: the intention and composition of the child's pallor, support from the family or parents, and organized activities. Disincentives and analysis: differences in personality. Caregivers must have many ideas, many suggestions. habits that he carried from their homes. Caregivers should advise incubators to continue to carry out existing activities at the orphanage with those who stay at home. The advocates and discouraging factors of caregivers chose to raise self-sufficiency: with strong intention, the child would voluntarily participate in activities at the orphanage. With the support of the family to provide child custody to the orphanage, it will make it easier for the orphanage to carry out the process of raising the child's self-sufficiency. With a schedule of organized activities, adoptive children will put themselves in activities at the orphanage. Personal differences in children make caregivers must be willing to confront the child with a bad personality and a sponsor. Differences in activities at home and in the orphanage affect children's habits of doing things.